Developing Service-Learners into Service-Leaders - Colby, Susan A.; Clark, Ann-Marie; Bryant, Jr., James Allen (International Journal of Research on Service-Learning in Teacher Education, 2014)
The purpose of this study was to examine the effects of one teacher education service-learning program that fosters the development of service-leaders through a carefully constructed sequence of experiences. Survey data collected from 141 preservice teachers were analyzed to identify what they learned over the course of their service-learning program and to determine areas for program improvement. The findings provided evidence that there were positive outcomes, both professional and personal, for preservice teachers enrolled in this program. Preservice teachers began to see the importance of providing service to the community and instilling a service ethic in the students they teach. They began to appreciate the impact that service-learning can have on their school community. Further, they overwhelmingly plan to use service-learning as a pedagogical tool in their future classrooms. Purposeful curriculum and program design can be a powerful catalyst for developing service-learners into service-leaders.